Prediction of Antimicrobial Peptides from Metatranscriptomic samples: A case study - Tuj-Johora, Fatema (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.